(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agricultural electricity subsidy plays a pivotal role in the Haryana’s agriculture landscape. The Agriculture sector of the state contributes significantly in the economy of Haryana and the food production for the nation. Electricity has become an indispensable resource in modern agriculture, and in Haryana, it has transformed the way farmers cultivate their lands. The government of Haryana has implemented agricultural electricity subsidies to support and incentivize farmers, making electricity more accessible and affordable for agricultural activities. This paper focuses on the status of government spending on the agricultural electricity subsidy in Haryana and examines the effects of electricity subsidy. The data were collected from the different government sites and report and other research articles. The spending on the agricultural electricity has been increasing from various years. Analysis implies that the agricultural electricity has a positive impact on the Gross State Domestic Products. But there is need for the target based policies so that subsidy will reach to the needy farmers and it also does not affect the efficiency of the energy utilities.